PENGGUNAAN MEDIA LOOSE PARTS UNTUK MENINGKATKAN KREATIVITAS ANAK USIA DINI - Fariyah Fariyah; Sugito Muzaqi (MOTORIC, 2023)
This research is motivated by the results of observations made that the existing learning methods are still lacking or have not found the right methods and media for children's creativity. The purpose of this research is to find out the application of the use of Loose Parts media to increase the creativity of early childhood. This research is descriptive qualitative research with data collection techniques through observation. The method of using Loose Parts media from natural materials as a medium in the learning process for Early Childhood plays a good role in increasing the creativity of students at Cahaya Bunda Kindergarten, Surabaya. By using Loose Parts media in the learning process, children become more enthusiastic and enthusiastic in participating in every activity given by the teacher. In addition to playing activities using Loose Parts media, children are given the widest possible opportunity to express themselves, provoke children's imagination and creativity without any limitations so that children become more optimal in their learning process. Keywords: Loose Parts media, Play, Creativity